Delay metric in wireless body area sensor net-works - E. Ramya, Mrs.; R. Gobinath, Dr (International Journal of Engineering and Technology, 2018)
Wireless Sensor Networks have the potential to greatly impact many aspects of medical care. This paper focuses on fundamental idea about the Protocols, standards, Technologies and measurements taken by the Researchers in the area of Wireless Body Area Sensor. This paper also listed various constraints in Wireless Body Area Sensor Networks and noticed the best suitable techniques for analyzing the Sensor Data. The quality of service is the most fundamental characteristics of any applications like Wireless Network, Wireless Sensor Network and Wireless Body Area Network. The performance factor in WBAN still remains trivial whereas performance issues are also a great concern. This paper given the effort to analyze and present some of the protocols and technologies developed toward performance issues in WBAN.Â Â